Glosa do wyroku SN z dnia 14 stycznia 2010 r., V KK 235/09 - Czopek, Krzysztof (Przegląd Prawno-Ekonomiczny, 2011)
Streszczenie dostępne wyłącznie w języku angielskim: The herein commented judgment by the Supreme Court concerns mainly the judicial fraud on the basis of Article 286 of the Penal Code. The author discuss the theme of disposal of property as set forth in Article 286, § 1 of the Penal Code as a result of fraud. This commentary analyzes also the issue of exclusion of a judge and prohibition of reformationis in peius. The Supreme Court’s opinions in this area deserve approval.